Evaluation of Paediatric Critical Care Needs and Practice in Nigeria: Paediatric Residents’ Perspective - Moses Temidayo Abiodun; Fidelis E. Eki-Udoko (Critical Care Research and Practice)
Background. There is a dire need for paediatric critical care (PCC) services, but their availability in tertiary hospitals in Nigeria is not well defined. Objective. We evaluated self-reported PCC practice, resources, and perceived challenges in various zones of the country, using paediatric residents’ perspective. Methods. This is a descriptive cross-sectional survey, carried out at an Intensive Course in Paediatrics at the University of Benin Teaching Hospital, Nigeria. Participants’ PCC practice and perceived adequacy of PCC resources and services were assessed using a 100 mm uncalibrated visual analogue scale (VAS). A comparison between northern and southern zones was done. A 2-sided p value < 0.05 was considered significant. Results. A total of 143 residents participated in the study, 37.1% of them were male, and 62.9% were female. Their mean age was 34.6 ± 3.2 years. They were mainly (86.7%) from federal institutions across the country. Less than a half (46.7%) of the trainees attended to critically ill children daily, but only 4 out of every 10 respondents stated that such severely ill children survived till hospital discharge; 12.1% of the trainees had PICUs in their institutions. Financial constraints hindered PICU admissions. PCC staff were relatively fewer in northern zones than southern zones (p<0.05). Their perceived adequacy of PCC equipment and services were low (VAS scores 32.7 ± 2.6 and 30.9 ± 2.8, respectively) with a strong positive correlation between the two measurements (r = 0.839; p<0.001). Conclusion. There is an unmet need for PCC practice in Nigerian tertiary hospitals with a resultant low survival rate of critically ill children. PCC training curricula and improved critical care resources are desirable in the setting.